1997
DOI: 10.1200/jco.1997.15.5.1994
|View full text |Cite
|
Sign up to set email alerts
|

Superantigen-based immunotherapy: a phase I trial of PNU-214565, a monoclonal antibody-staphylococcal enterotoxin A recombinant fusion protein, in advanced pancreatic and colorectal cancer.

Abstract: PNU-214565, a SAg-based tumor targeted therapy, is safe when given as a single 3-hour infusion at doses up to 1.5 ng/kg. The MTD for a single dose was not determined. The safety of a repeated dose schedule is currently under investigation, beginning with doses determined to be safe in this trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…[2][3][4][5] There are several reports that have demonstrated the effectiveness of some targeted strategies involving monoclonal antibodies or immunotoxins to treat pancreatic cancer. 3,42 These approaches were limited because expression of the target antigens was insufficient to deliver targeting agents in sufficient quantity to eliminate all cancer cells. 43 Our approach overcomes this problem as gene transfer of only one chain of a cytokine receptor system binds significant molecules of cytotoxin to cause profound antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] There are several reports that have demonstrated the effectiveness of some targeted strategies involving monoclonal antibodies or immunotoxins to treat pancreatic cancer. 3,42 These approaches were limited because expression of the target antigens was insufficient to deliver targeting agents in sufficient quantity to eliminate all cancer cells. 43 Our approach overcomes this problem as gene transfer of only one chain of a cytokine receptor system binds significant molecules of cytotoxin to cause profound antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although many approaches are employed to treat this malignancy including surgery and chemotherapy, median survival following diagnosis is only 6 months, which has not improved in the past 30 years. [2][3][4][5] An effective new approach against this disease is desperately needed.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recombinant fusion protein of the tumor-reactive mAb and SEA (Fab-SEA) expressed a 100-fold stronger affinity for the tumor antigen than MHC class II molecules. 9 In vitro and in vivo studies have shown that Fab-SEA could target cytotoxic T cells against MHC class II − tumor cells bearing the proper tumor antigen in the absence of obvious systemic side-effects, [10][11][12][13][14][15][16][17] which demonstrated functional substitution of the MHC class II-dependent presentation of SEA with tumor specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic fusion proteins, MHC class II-independent and tumor-specific, have been evaluated successfully. 23,24,[51][52][53][54][55] In summary, the preclinical findings indicate that SEB could be a useful agent for treatment of bladder cancer and that a clinical phase I evaluation appears warranted. …”
Section: Discussionmentioning
confidence: 97%
“…In vivo, the application leads to transient expansion and subsequent death of T cells with the appropriate V b s. [7][8][9] The characteristics of superantigens can be exploited in diseases where strong immunologic responses are required. This effect has been evaluated in several preclinical [10][11][12][13][14][15][16][17][18][19][20][21][22] and clinical [23][24][25][26] studies of immunotherapeutic approaches in the treatment of cancer where superantigens were used as adjuvant or in fusion molecules with specific antibodies to enhance or maintain the immunologic response. Superantigen administration significantly enhances ineffective antitumor immune responses, resulting in potent and long-lived protective antitumor immunity.…”
mentioning
confidence: 99%